Exploring the factors that influence the success of youth-owned MSMEs funded through microfinance funding: the case of the National Youth Development Agency (NYDA) - Tsoai, Unathi (Graduate School of Business (GSB), 2026)
This study investigates the factors influencing the success of youth-owned Micro, Small, and Medium Enterprises (MSMEs) funded through microfinance by South Africa's National Youth Development Agency (NYDA). With youth unemployment remaining one of the country's most pressing challenges, the research explores how microfinance and non-financial support, such as mentorship and training, impact the sustainability and growth of youth-owned businesses. At its heart, the study gives voice to six young entrepreneurs, sharing their lived experiences and the real-world complexities they face. Using a qualitative, exploratory case study approach, data was gathered through semi- structured interviews with NYDA grant recipients, supported by document analysis and triangulation with official NYDA reports. The study draws on the Resource-Based View (RBV) and Institutional Theory to understand how internal strengths and external support systems interact to influence business success. Findings highlight that entrepreneurial success is shaped not only by access to funding but also by personal resilience, curiosity, the availability of relevant business support services, and strong mentorship. However, challenges such as slow funding processes, limited market access, and poor communication from support institutions emerged as common pain points. Still, the overall perception was that NYDA's intervention had a positive impact on both business growth and the confidence of the entrepreneurs themselves. By offering grounded, context-specific insights into youth entrepreneurship, this study contributes meaningfully to the growing body of knowledge on microfinance in emerging economies. Its recommendations aim to help refine public support programmes, making them more responsive, inclusive, and impactful for the next generation of business leaders in South Africa.